Evaluation of Renal Adverse Effects of Combination Anti-retroviral Therapy including Tenofovir in HIV-infected Patients - Hiroyuki Tanaka; Mariko Arai; Yoshinori Tomoda; Tatsuhiko Wada; Kazuo Yago; Mitsutoshi Satoh (Frontiers Media S.A., 2013)
Purpose. In order to maintain plasma HIV-RNA concentration in HIV-infected patients, below the detection limit combination anti-retroviral therapy (cART) are used. Although the nucleoside/nucleotide reverse transcriptase inhibitor, tenofovir disoproxil fumarate (TDF) is a first-line drug commonly used, it is associated with renal dysfunction. Nevertheless, only few clinical studies have focused on TDF in combination with new anti-HIV drugs, including the protease inhibitor (PI) darunavir (DRV), or the integrase strand transfer inhibitor (INSTI) raltegravir (RAL). Here we report the influence of such cART involving TDF on renal function.　Methods. We retrospectively investigated 68 patients under cART that included TDF between November 2004 and May 2012. We used hospital records to establish each patient's background and characteristics, CD4 cell count, plasma HIV-RNA concentration, drug combinations, renal function, and anti-retrovial therapy history. Results. In all patients who had received cART, the plasma HIV-RNA concentration had fallen to less than 40 copies/mL by week 24 after the start of the therapy, and an increase in the CD4 cell count was observed. For each drug used in combination with TDF, the plasma HIV-RNA concentration and CD4 cell count showed a similar trend. After week 12, the estimated glomerular filtration rate (eGFR) had significantly decreased in all patients. The eGFR was significantly lower in those received PI on week 24 and in those received INSTI on week 12. The eGFR was significantly reduced in PI group who received atazanavir + ritonavir (ATV/RTV) on week 60. The eGFR in the DRV/RTV group tended to decrease. The eGFR in the PI and ATV/RTV group was significantly lower than in the efavirenz (EFV) group on week 96. Conclusion. It selecting drugs to include in combination therapy of HIV-infected patients, consideration should be given to the risk of renal dysfunction. There is a need to monitor renal function when TDF is combined with ATV/RTV, DRV/RTV or RAL. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.